PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI (Studi Empirirs Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2014 – 2016) - Alfonsia Klofilda Suryati; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (Forum Manajemen STIMI Handayani Denpasar, 2019)
The value of firm is something that can be seen through several share prices of the firm itself. To increase value of the firm, they should escalate consumer reliance, and conducting social responsibility is one way to increase society reliance to the company so as to increase the value of the firm itself. This study aims to determine the effect of corporate social responsibility to value of the company with profitability as moderating variable.The population used in this study are the mining companies registered in Bursa efek Indonesia period 2014 – 2016. Purposive sampling is method used in this research with the sample as much as 19 mining companies. MRA (Moderated Regression Analisys) is used as data analisys technique with interaction tests. The results of the study show that corporate social responsibility variables do not affect the firm value. Profitability as a moderating variabels cannot moderate correlation between Corporate Social Responsibility with firm value. However, profitability as independent variable has an affect to firm value.